Assessing the Economic Impacts of Local Food System Producers by Scale: A Case Study From New York. (November 2016) - Schmit, Todd M.; Jablonski, Becca B. R.; Mansury, Yuri
Policy makers and economic developers are increasingly interested in the impacts of local food systems, yet attempts to obtain accurate estimates are often complicated by a lack of available data. Utilizing a unique data set from producers in New York, the authors examine the extent of differential purchasing and sales patterns for small-scale direct agriculture (SDA) producers. The supplemental data are integrated into a regional input–output model to assess the total effects and distributional implications of equivalent policies targeted to agriculture sectors. The authors demonstrate that SDA producers have different expenditure patterns than other agricultural producers and, for equivalent policy shocks targeted toward agriculture industry expansion, have lower total employment and output impacts but higher effects on labor income and total value added than non-SDA producers. The results underscore the importance of collecting appropriate data for analysis and outline the local economic benefits of small-scale local food system participants.